Mirʾāt al-akwān : Taḥrīr-i Sharḥ-i Hidāya-yi Mullā Ṣadrā Shīrāzī - Ardakānī, Aḥmad b. Muḥammad Ḥusaynī, (Miras Maktoob, ISBN: 9789004365452., 2018)
Aḥmad Ḥusaynī Ardakānī's (d. 1242/1826-7) Mirʾāt al-akwān is a Persian adaptation of Ṣadr al-Dīn Shīrāzī's (d. 1050/1640) Sharḥ al-Hidāya , a commentary on Athīr al-Dīn al-Abharī's (d. ca 663/1264) seminal philosophical summa the Hidāyat al-ḥikma . The Hidāya has been of tremendous influence in the Islamic world, producing a huge commentary tradition. Ṣadr al-Dīn Shīrāzī's commentary yielded its own series of glosses and commentaries, and in India it even became a foundational text in the madrasas. Ardakānī is mostly known as a translator of religious and philosophical works. He wrote the present adaptation at the request of Muḥammad Walī Mīrzā (d. 1285/1869), a son of Fatḥ ʿAlī Shāh Qājār (d. 1249/1834). The Mirʾāt al-akwān covers just the physics and the metaphysics, leaving out the logic after the example of Shīrāzī. The metaphysics part being lost, the editor added the section on metaphysics of Ardakānī's translation of Shīrāzī's al-Mabdaʾ wal-maʿād , published earlier by him.